Who should be screened for primary aldosteronism? A comprehensive review of current evidence - Huang, Wei Chieh; Lin, Yen Hung; Wu, Vin-Cent; Chen, Chen Huan; Siddique, Saulat; Chia, Yook Chin *; Tay, Jam Chin; Sogunuru, Guru Prasad; Cheng, Hao Min; Kario, Kazuomi (Wiley, 2022)
Arterial hypertension is a major risk factor for cardiovascular disease. The prevalence of primary aldosteronism (PA) ranges from 5% to 10% in the general hypertensive population and is regarded as one of the most common causes of secondary hypertension. There are two major causes of PA: bilateral adrenal hyperplasia and aldosterone-producing adenoma. The diagnosis of PA comprises screening, confirmatory testing, and subtype differentiation. The Endocrine Society Practice Guidelines for the diagnosis and treatment of PA recommends screening of patients at an increased risk of PA. These categories include patients with stage 2 and 3 hypertension, drug-resistant hypertension, hypertensive with spontaneous or diuretic-induced hypokalemia, hypertension with adrenal incidentaloma, hypertensive with a family history of early onset hypertension or cerebrovascular accident at a young age, and all hypertensive first-degree relatives of patients with PA. Recently, several studies have linked PA with obstructive sleep apnea and atrial fibrillation unexplained by structural heart defects and/or other conditions known to cause the arrhythmia, which may be partly responsible for the higher rates of cardiovascular and cerebrovascular accidents in patients with PA. The aim of this review is to discuss which patients should be screened for PA, focusing not only on well-established guidelines but also on additional groups of patients with a potentially higher prevalence of PA, as has been reported in recent research.